Status Gizi, Ventilasi, Kebiasaan Merokok Dan Peran Tenaga Kesehatan Dengan Kejadian TB Paru - Neila Sulung; Nunung Gus Amalia (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
Tuberculosis (TB) is still a major health problem. In 2017, 36 cases of Tuberculosis were recorded in the work area of Rasimah Ahmad Public Health Center in Bukittinggi, which is the highest number of all Health Center. The aim of the study was to determine the relationship of nutritional status, ventilation, smoking habits and the role of health workers with the incidence of pulmonary TB. This study uses an observational method with a case control approach. There are 2 populations consisting of 36 case populations and 36 control populations with total sampling and purposive sampling techniques with a sample ratio of 1: 1. Data analysis was performed using univariate and bivariate analysis. The results of the study obtain that there was a relationship between nutritional status (pvalue = 0,000, OR = 9,416), smoking habits (p value = 0,008, OR = 4,375) and the role of health workers (p value = 0,000, OR = 7,000). And there was also no correlation between ventilation and the incidence of pulmonary tuberculosis (pvalue = 1,000 and OR = 1,000). Conclusion variables that have a lot of chance of risk for the incidence of pulmonary TB are nutritional status. It is recommended to maintain the diet by eating according to nutritional needs and regularly.